O clube de inglês de um colégio militar como uma prática colaborativa e transformadora: percepções dos participantes frente a uma perspectiva sociocultural - Martin, Daniela Roza (Universidade do Vale do Rio dos Sinos, 2021)
It is common nowadays to see in learners the desire to build knowledge in different spaces that are not only limited to the regular classroom. In this context of learning emerges the musical project performed in English by students from the English Club of a military school in the state of Rio Grande do Sul. This extracurricular activity was initiated by the students themselves, having as objective more than their own cognitive development. Through this project, it is aimed to encourage learners’ empowerment towards a collaborative and transformative education, and subsequently, contribute to the socio-historical-cultural development of those involved. Thus, this case study aims to analyze the importance of the formation of the community of practice (CoP) for the collaborative and transformational development of English learners in extracurricular activities. The research lasted four months and counted on the participation of six members from the English Club selected for this research, as well as the two guiding teachers in charge of the project. Due to Covid-19 pandemic, the data generation was obtained exclusively remotely. It was used as instruments a memoir of one of the musical pieces, an initial questionnaire, some data obtained from conversation wheel and the narratives generated through individual semi-structured interviews with each participant. From the generated data, it was identified that this acting project brought to discussion some concepts of socio-cultural matrix that constitute the Collaborative and Transformative learning model (ACT), they are investment, agency, autonomy and perezhivanie. Through the triangulation of data, we sought to recognize the English Club as a real community of practice, reflecting on the role of emotions in this context and the resignification of the development of the participants' additional language, which resulted in a reflection of the school as a space of social transformation, where language is seen as an end and a means to collaborate with the development of other areas of knowledge.
Keywords: Colégio Militar; Língua adicional; Aprendizagem Colaborativa e Transformadora (ACT); Comunidade de Prática (CoP); Military School; Additional language; Collaborative and Transformative Learning (CTL); Community of Practice (CoP); ACCNPQ::Lingüística, Letras e Artes::Lingüística